Effect of Ultrasonic During Preparation on Cu-Based Catalyst Performance for Hydrogenation of C02 to Methanol - M Nasikin; A Wahid (Department of Chemical Engineering, Universitas Gadjah Mada, 2005)
Indonesia is rich in natural gas resources. These resources contain hydrocarbons and impurities such as C02. C02 creates a difficulty in further gas treatment and also becomes an environmental problem. Therefore, it is needed to develop a concept to recover this kind of gas and to convert it into more useful chemicals. Catalytic hydrogenation to methanol is one of the technologies that can be considered. Conversion of C02 to methanol can be catalyzed by Cu-based catalyst. Reported tobe the best catalyst, this catalyst is selected as a catalyst for a pilot plant that is operated at a high pressure and a high temperature. However, further development is needed to rearrange the synthesis to be operated both at lower pressure and temperature. For this system, it is needed to increase its catalytic activity. One of the alternatives is to apply a catalyst preparation method using ultrasonic effect. In this research work, CuO/ZnO/AJp3 catalyst with Cr as a promoter was prepared by co-precipitation method. The effect of ultrasonic on catalyst performance, which was irradiated to the catalyst during preparation, was investigated. Co-precipitation was conducted by using carbonate salt for respective metal cations added to the catalyst. Ultrasonic wave was irradiated to the catalyst preparation chamber with 40kHZ and time variable. The characteristics of the catalyst were analyzed by BET method for surface area, while SEM and H2 chemical adsorption were conducted to determine active site dispersion. A high-pressure continuous flow reactor was used for catalyst activity and stability test. The test was conducted at an operation condition of 30 bars and 200-30QoC. The effect of ultrasonic on the CuO/ZnO/AJp3 catalyst shows that ultrasonic irradiation enhances the catalyst surface from 23 to 50 m2/g. SEM analysis shows the change of catalyst morphology to be more uniform and the catalyst particle becomes smaller. The activity test shows that the catalyst with 60 min irradiation time has the highest activity in the hydrogenation of C02 to methanol at 30 bars and at 275°C. Keywords: Hydrogenation, dispersion, methanol, and ultrasonic.